Direct Cost Analysis of Hypertension in National Health Insurance Participants for the Advanced Level Healthcare in Indonesia : Analysis of BPJS Kesehatan Sample Data 2023 - Akhmal Raziq Kharazi; Bambang Budi Raharjo (Lembaga Pengembangan Kinerja Dosen, 2025)
In 2023, WHO states one-third of individuals aged 30-79 have hypertension, only 42% receive treatment, and few of just 20% that receive it are controlled. Indonesia’s 2020-2022 Health Profile shows an annual increase of catastrophic disease burdened by the National Health Insurance (NHI), particularly for outpatient and inpatient advanced-level care. NHI’s Statistics of 2020-2021 reports increased utilization of healthcare services for hypertension-related visits from 2020 to 2021. This condition may cause an increase of economic burden to the healthcare system and pose financial risk for its participants. This study examines factors influencing the direct costs of hypertension-related visits among NHI participants at an advanced level. This study uses an analytical observational quantitative approach with a cohort design, utilizing the 2023 BPJS Kesehatan Sample Data. The total sampling method resulted in a total of 26.776 participants and 102.748 visits that were analyzed, with weighted results representing 2.207.606 participants and 8.583.700 visits. Data analysis included univariate, bivariate (simple logistic regression), and multivariate (multiple logistic regression) methods. Significant factors (p-value<0.05) affecting outpatient costs include age, regional type, administrative status, health facility ownership, and health facility type. Inpatient costs are influenced (p-value<0,05) by gender, regional type, class entitlement, health facility ownership, health facility type, comorbidities, length of stay, and severity. The study recommends evaluating advanced level healthcare tariff policies to minimize economic disparities in healthcare access across Indonesia.